Increased 8-isoprostane, a marker of oxidative stress in exhaled breath condensate in subjects with asbestos exposure - Pelclová, Daniela; Fenclová, Zdenka; Kacer, Petr; Kuzma, Marek; Navrátil, Tomás; Lebedová, Jindriska (Industrial health, 2008)
Asbestosis and pleural plaques exhibit unpredictable but progressive development, and there are no markers routinely available to measure their prognosis. Asbestos exposure induces the generation of reactive oxygen species, and 8-isoprostane is involved in experimental asbestos-related lung toxicity. This oxidative stress marker was measured in exhaled breath condensate (EBC) in 92 former asbestos workers with mean age 68.8+/-1.7 yr and mean duration of asbestos exposure 24.1+/-2.0 yr. The control group had 46 subjects with mean age 65.2+/-3.3 yr. The mean level of 8-isoprostane, analyzed by liquid chromatography-electrospray ionization-mass spectrometry, was higher in asbestos-exposed subjects (69.5+/-6.6 pg/ml, p=0.0001) compared with the control group, where the concentration was 47.0+/-7.8 pg/ml. The results presented support the hypothesis that oxidative stress due to asbestos is the main cause of increased 8-isoprostane in EBC. Measurement of 8-isoprostane in EBC is a promising non-invasive means for assessing the activity of asbestos-induced diseases.
Keywords: Asbestosis; hodnocení rizik; Female; Asbestos; biologické markery; oxidační stres; Biomarkers; ženské pohlaví; Oxidative Stress; lidé; Occupational Exposure; studie případů a kontrol; Aged, 80 and over; dinoprost; azbestóza; Breath Tests; Risk Assessment; prognóza; Male; azbest; pracovní expozice; Aged; Case-Control Studies; Prognosis; Dinoprost; lidé středního věku; dechové testy; senioři nad 80 let; senioři; mužské pohlaví; Middle Aged; Humans